Kesenian Profetik Membangkitkan Khittoh Seni Back To Basic (Telaah Kesenian dan Keislaman) - Wawan Kardiyanto (Institut Seni Indonesia Surakarta, 2019)
Currently there is a flourishing art creations that is influenced by the concept and / or theory of art for art (L'art pour L'art), which tends to show value-free art creations, which tend to emphasize ethical, aesthetic, and truth values. The prophetic mission of religion is a prophetic movement through theology which becomes a revolutionary ideology, which always brings about changes in civilization. Here the prophetic ethics movement in religions becomes grounded to be a social implementation including art. This article tries to think about the concept of prophetic art that will give more beneficial and clear goals of the arts, namely to remain in synergy with the interests of ethics, aesthetics and truth. This study uses a Heuristic analysis approach with the literature method. The conclusion tells that prophetic art is a positive concept for the development of artistic paradigms which are proven to be necessary to develop as a concept of purpose and the value of art. Prophetic art in Islamic teachings is something important to be an offering for creative method of sharing. Islamic and prophetic art will make people's lives more beautiful in the prescribed Islamic law.